2018
DOI: 10.1002/adma.201800737
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Nonfullerene Polymer Solar Cells Enabled by a Copper(I) Coordination Strategy Employing a 1,3,4‐Oxadiazole‐Containing Wide‐Bandgap Copolymer Donor

Abstract: A novel wide-bandgap copolymer of PBDT-ODZ based on benzo[1,2-b:4,5-b' ]dithiophene (BDT) and 1,3,4-oxadiazole (ODZ) blocks is developed for efficient nonfullerene polymer solar cells (NF-PSCs). PBDT-ODZ exhibits a wide bandgap of 2.12 eV and a low-lying highest occupied molecular orbital (HOMO) level of -5.68 eV, which could match well with the low-bandgap acceptor of 3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone)-5,5,11,11-tetrakis(4-hexylthienyl)-dithieno[2,3-d:2',3'-d']-s-indaceno[1,2-b:5,6-b']-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 49 publications
0
54
0
Order By: Relevance
“…Besides, peak‐differentiating analysis showed that one more diffraction peak located at q xy = 0.386 Å −1 ( d = 16.3 Å, Figure S8, Supporting Information), which might originate from the backbone ordering due to the end‐group π–π stacking . Compared to the pristine polymer films, the (100) diffraction turned from semicircle to more preferred q xy direction, indicating the enhanced face‐on packing, which would be beneficial for vertical charge transport . The PNDT‐ST:Y6‐T binary blend showed higher ordered structures with multiple peaks than PNDT‐ST:Y6‐T binary blend.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, peak‐differentiating analysis showed that one more diffraction peak located at q xy = 0.386 Å −1 ( d = 16.3 Å, Figure S8, Supporting Information), which might originate from the backbone ordering due to the end‐group π–π stacking . Compared to the pristine polymer films, the (100) diffraction turned from semicircle to more preferred q xy direction, indicating the enhanced face‐on packing, which would be beneficial for vertical charge transport . The PNDT‐ST:Y6‐T binary blend showed higher ordered structures with multiple peaks than PNDT‐ST:Y6‐T binary blend.…”
Section: Resultsmentioning
confidence: 98%
“…The facile side chains provide the tunable bandgaps and molecular energy levels at the same time . For those reasons, BDT‐based donor polymers have dominated the most efficient PSCs . Compared with BDT, the extended π‐conjugation system of naphthodithiophene (NDT) is expected to produce the higher backbone coplanarity and affords stronger intermolecular orbital overlap, facilitating π‐electron delocalization along the backbone and inducing strong co‐facial π–π stacking for improving charge transport behavior .…”
Section: Introductionmentioning
confidence: 99%
“…We admit that such complexation strategy may be not unexceptionable from the perspective of industrialization. Only those polymer donors with specific polynitrogen heterocyclic skeletons can work well, and the complexation process increases the synthetic complexity and cost. Regardless of that, our work provides a new and efficient method for easy optimization of morphology in PSCs, which also can help us better understand the relationship of molecular structure and property.…”
Section: Photovoltaic Parameters Of the Nf‐pscsmentioning
confidence: 99%
“…In terms of active blend morphology, it is widely accepted that the nanoscale phase separation with the bicontinuous interpenetrating networks and the domain sizes in the range of 10–20 nm is critical for efficient exciton diffusion and dissociation . It is worth noting that such ideal morphology actually results from the joint effects of various factors, including the natural properties of the semiconductors (solubility, crystallinity, miscibility, etc.…”
Section: Photovoltaic Parameters Of the Nf‐pscsmentioning
confidence: 99%
“…[1][2][3] Electron-deficient groups, such as rhodanine (RH), 4,5 1,3-indandione (IN), 6,7 and 1,1-dicyanomethylene-3-indanone (CNIN) 8,9 have been widely used as acceptor units, together with fused-ring-based electron-rich groups, such as carbazole (Cz), 10,11 fluorene (Flu), 12,13 indacenodithiophene (IDT), 14,15 and indacenodithienothiophene (IDTT). Non-fullerene acceptors (NFAs) composed of donor (D) and acceptor (A) units have been widely reported due to their high power conversion efficiencies (PCEs) exceeding 14%.…”
Section: Introductionmentioning
confidence: 99%